Expressing silence where language and culture meet in Japanese - Tsujimura, Natsuko (Lexington Books, 2022)
"In Expressing Silence: Where Language and Culture Meet in Japanese, Natsuko Tsujimura discusses how silence is conceptualized and linguistically represented in Japanese. Languages differ widely in the specific linguistic and rhetorical modes through which vivid depictions of silence are achieved. In Japanese, sounds coming from insects, small animals, ocean waves, and leaves all evoke silence, and onomatopoeia plays an important role in simulating silent scenes. These linguistic mechanisms mediate the perception of the symbiotic relationship between sound and silence, a perception deeply embedded in the Japanese cultural experience. Drawing from a wide variety of rhetorical samples, Expressing Silence brings the tools of both linguistic and cultural analysis to bear in examining the remarkably rich array of representations of silence in Japanese language and culture. She finds that depictions of silence through language cannot be understood without exploring what sound or silence mean to the speakers. She analyzes a cluster of sounds in nature and onomatopoeic vocabulary for verbal portrayals of silence, consistent with a cultural pattern of practices that value sensate and affective reactions"--